Weak thixotropic, anti-settling and heat-conducting epoxy pouring sealant and preparation method thereof

By performing the surface treatment of the star branched anti-settler on the gas phase silica, combined with an appropriate amount of acid anhydride and thermally conductive powder, a weak thixotropic and anti-settled thermal epoxy potting adhesive was prepared, which solved the problem of sedimentation stability after adding the thermal powder, and achieved a comprehensive improvement of thermal conductivity, anti-settled and fluidity.

CN119570419APending Publication Date: 2025-03-07FOSHAN SANSHUI JINGE NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411816740.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

After adding thermally conductive powders, especially in the acid anhydride components, existing epoxy potting glues are prone to static placement settlement and hard plate bonding, and the settlement phenomenon is more obvious when the viscosity is low.

Method used

A preparation method is adopted to prepare a weak thixotropic and anti-saltitude thermal epoxy potting adhesive that is weakly thixotropic and anti-saltitude by surface treatment of star branched anti-saltitude agent on the gas phase silica, combined with an appropriate amount of acid anhydride and thermally conductive powder. The method includes adding epoxy resin, acid anhydride, thermally conductive powder and star-shaped branched anti-settling agent to the reaction kettle, stirring and mixing, vacuum defoaming, and finally potting and curing.

Benefits of technology

The epoxy potting glue prepared by this method not only maintains good thermal conductivity, but also significantly improves the resistance to settling and fluidity, can maintain good dispersion and stability under static and dynamic conditions, and has strong toughness and crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182021050000021
    Figure BDA0005182021050000021
  • Figure BDA0005182021050000031
    Figure BDA0005182021050000031
  • Figure BDA0005182021050000041
    Figure BDA0005182021050000041
Patent Text Reader

Abstract

The invention relates to a weak thixotropic, anti-settling and heat-conducting epoxy pouring sealant and a preparation method thereof, nano silicon dioxide, secondary amino silane, polyether glycol, isocyanate and other raw materials are adopted, a star-shaped branched anti-settling agent is prepared through a two-step process, and the star-shaped branched anti-settling agent is applied to a component A and a component B of the heat-conducting and flame-retardant epoxy pouring sealant. The component A and the component B can be uniformly mixed and stirred according to the mass ratio of 1: 1, vacuum defoaming is performed to obtain the heat-conducting flame-retardant epoxy pouring sealant, and during actual use, the pouring sealant can be injected into a device needing to be packaged and cured for 2 hours at the temperature of 120 DEG C, so that the heat-conducting flame-retardant epoxy pouring sealant is obtained. The star-shaped branched anti-settling agent prepared by the invention has a good anti-settling effect in the pouring sealant and effectively improves the high and low temperature cracking resistance of a cured product of the epoxy pouring sealant at the same time, and a packaging material formed by the cured product has the advantages of excellent sealing performance, long-term durability and stability and the like; the material can be widely applied to the fields of electronics, 5G, low-altitude aircrafts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of potting and packaging of electronic appliances, and in particular relates to a method for preparing a powder surface treatment and a heat-conducting epoxy potting adhesive with weak thixotropy, anti-settling and good fluidity. Background Art

[0002] Epoxy resin has become the preferred material for coatings, adhesives, electronic packaging materials, structural adhesives, etc. due to its high strength, high hardness, good adhesion, excellent electrical insulation, chemical resistance and stability. As electronic devices develop towards thinness, integration and high frequency, the heat generated per unit volume has increased significantly. The accumulated heat not only seriously affects the operating reliability of electronic devices, but also shortens the service life. Since the thermal conductivity of pure epoxy resin is only 0.17~0.23W / k*m, in order to improve the thermal conductivity of epoxy resin, adding thermal conductive powder (aluminum oxide, aluminum hydroxide, silicon powder, boron nitride) to epoxy resin is currently an important means to improve the thermal conductivity of epoxy resin. In order to achieve a higher thermal conductivity, it is often achieved by significantly increasing the proportion of thermal conductive fillers added, but these thermal conductive fillers such as aluminum oxide will settle and harden as the placement time increases under high filling in the resin, especially in the low viscosity anhydride component. Existing studies such as CN111944468B and CN111087942B proposed to improve the anti-settling property and filler dispersibility of the resin by surface modification of thermal conductive fillers (such as α-alumina powder or crystalline silica powder) and adding fumed silica and other anti-settling agents. However, directly adding fumed silica will lead to an increase in the viscosity and thixotropy of the system, affecting the leveling of the finished product.

[0003] In order to prevent the above problems, researchers in related industries use silane coupling agents, dispersing agents, etc. to modify the surface of thermal conductive powders. Improve the interface interaction between thermal conductive fillers and the matrix, improve the dispersibility of fillers in the resin matrix, etc., thereby reducing their sedimentation rate; in addition, by adding anti-settling agents such as fumed silica, bentonite, organic montmorillonite, attapulgite, etc., changing the thixotropic ratio of the system, the suspension stability of the filler can also be improved to slow down the sedimentation rate. Among them, fumed silica with small particle size, large specific surface area, high surface activity, and good stability under high temperature conditions has become the first choice for potting glue to resist sedimentation, but the surface of fumed silica that has not been surface treated is multi-hydroxyl, has strong water absorption, is difficult to disperse, and even if the initial dispersion is evenly placed, secondary agglomeration will occur. Therefore, the corresponding surface treatment of fumed silica has become the focus of researchers. CN111944468B discloses a two-component heat-conducting flame-retardant epoxy resin potting glue and its preparation method and application. In this method, KH-560 is used to modify the surface of α-alumina powder or crystalline silicon powder, and fumed silica is added at the same time to improve the dispersibility, compatibility and anti-settling property of the heat-conducting filler. CN111087942B discloses a potting glue composition that uses fumed silica and organic bentonite in combination with a viscosity reducer to improve the anti-settling property of the resin part of the pre-added filler while ensuring the viscosity of the system. Although the above-mentioned method of directly adding fumed silica can improve the dispersibility and anti-settling property of the filler in the resin matrix, fumed silica is difficult to disperse and will also increase the viscosity and thixotropy of the system, affecting the leveling property of the finished product.

[0004] Therefore, how to maintain the dispersibility and anti-sedimentation properties of the system while avoiding excessive influence on the viscosity and thixotropic ratio of the system through surface treatment of fumed silica, so as to solve the sedimentation stability problem of thermal conductive fillers in epoxy resin potting glue, especially maintaining good dispersibility and stability during long-term static and dynamic transportation and storage is the current research focus. Summary of the invention

[0003] The present invention aims to solve the problem in the prior art that epoxy potting glue is prone to static sedimentation and hardening when adding thermal conductive powder, especially anhydride components, which is more obvious in anhydride components with relatively low viscosity. Provided is a method for preparing a weakly thixotropic epoxy potting glue with good anti-settling performance. The epoxy potting glue prepared by the method has good anti-settling performance under static conditions and dynamic transportation simulation while ensuring the thermal conductivity of the potting glue. At the same time, the longer organic chain segment not only improves the resin compatibility, but also improves the toughness and high and low temperature impact resistance of the epoxy.

[0004] The weak thixotropic, anti-settling thermally conductive epoxy potting adhesive of the present invention has the following components in proportion: Preparation method of component A: first add epoxy resin into the reaction kettle according to weight percentage, raise the temperature to 40-70°C, stir, rotate at 200-1500r / min, add each material into the epoxy resin, stir and mix evenly, and vacuum degas to obtain component A; The proportion of each material in component B (weight percentage): Anhydride: 20-45% Thermal conductive powder: 50-75% Star-branched anti-settling agent: 0.5-5% Preparation scheme of component B: first add acid anhydride into the reaction kettle according to weight percentage, stir at room temperature, add various materials into the acid anhydride at a speed of 200-1500r / min, stir and mix evenly, and vacuum degas to obtain component B; Preparation of epoxy potting adhesive: Mix component A and component B prepared in the above steps in a mass ratio of 1:1, stir evenly, perform vacuum degassing, potting, and curing to obtain a thermally conductive flame-retardant epoxy potting adhesive.

[0005] The epoxy resin in the component A is one or more of bisphenol epoxy resin, glycidyl ester epoxy resin, aliphatic epoxy resin, alicyclic epoxy resin and heterocyclic epoxy resin.

[0006] The active diluent is one or more of a monofunctional epoxy diluent, a difunctional epoxy diluent and a multifunctional epoxy diluent.

[0007] The thermal conductive powder is one or more of aluminum hydroxide, aluminum oxide, silicon powder, boron nitride, aluminum nitride, diamond, silicon nitride, etc., and its particle size is: D50: 0.5-100 microns.

[0008] The acid anhydride is one or more of phthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride and the like.

[0009] The defoaming agent is FD-940, the coupling agent is 3-glycidyloxypropyltrimethoxysilane SCA-E87M, and the flame retardant is a phosphorus-nitrogen flame retardant.

[0010] The star-branched anti-settling agent has the following preparation process: STEP 1: Disperse 5 to 25 parts of nano-silica in 100 parts of anhydrous ethanol solvent, with the mass proportion of nano-silica in anhydrous ethanol being 5% to 25%. After uniform dispersion, gradually drop 0.025 to 1.5 parts of aminosilane solution pre-hydrolyzed by deionized water, with the mass proportion of aminosilane coupling agent in fumed silica being 0.5% to 15%. After the reaction is completed, remove ethanol by rotary evaporation and dry at a drying temperature of 100 to 150°C to obtain aminosilane-modified nano-silica for later use; STEP 2: 10-300 parts of aminosilane-modified nano-silica prepared in Step 1 and 1000 parts of urethane-grade solvent are placed in a dry reaction container and stirred, and then 0.5-2.0 parts of hydantoin epoxy resin solution are added, the reaction temperature is 10-30°C, and the reaction time is 0.5-3.0h; and 0.5-5.0 parts of polyether diol and isocyanate are added dropwise respectively. After the addition is completed, the reaction is carried out again, the reaction temperature is 50-75°C, and the reaction time is 0.5-3.0h. Dry nitrogen is passed through the whole reaction process. After the reaction is completed, the star-branched anti-settling agent is obtained by solvent washing and rotary evaporation, in which the organic component accounts for 0.5% to 15% of the gas phase silica. The reaction formula for its preparation is as follows: The solvents selected in step 2 of this process are urethane-grade toluene and xylene; Silicon dioxide used: primary particle size: 1-100nm, specific surface area: 25-500m 2 / g; The aminosilane used is a secondary aminosilane, such as N-(2-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-(N-cyclohexylamino)propyltrimethoxysilane, N-(n-butyl)-3-aminopropyltrimethoxysilane, N-(n-butyl)-3-aminopropyltriethoxysilane, bis(3-triethoxysilylpropyl)amine, bis(3-trimethoxysilylpropyl)amine, etc.; The hydantoin epoxy resin used is: its structural formula is as shown in the figure below, n value is 1 to 6, epoxy value is 0.2 to 0.75 mol / 100 g, preferably 0.44-0.70 mol / 100 g; The polyether diol used is ethylene oxide-propylene oxide diol, and its relative molecular weight is 400-2000; The isocyanate used is one or more of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), hydrogenated MDI and the like.

[0011] Preparation method of component A: According to weight percentage, add each material of component A to epoxy resin in sequence under stirring condition, stir and mix evenly, and vacuum degas to obtain component A; wherein, the order of adding each material of component A has no effect on the preparation of component A. Preparation of component B: According to the weight percentage, add each material of component B to the acid anhydride in sequence under stirring conditions, stir and mix evenly, and vacuum degassing to obtain component B; wherein, the order of adding each material of component B has no effect on the preparation of component A. Preparation of potting glue: Mix component A and component B prepared in the above steps at a mass ratio of 1:1, stir evenly, and vacuum degassing to obtain thermal conductive flame retardant epoxy potting glue. In actual use, the potting glue can be injected into the device to be encapsulated and cured at 120°C for 2h.

[0012] Compared with the prior art, the beneficial effects of the present invention are that the prepared epoxy potting adhesive has good thermal conductivity, low thixotropic ratio, good fluidity, and good static and dynamic anti-settling properties, as follows: (1) The epoxy potting compound prepared by the present invention has excellent anti-settling properties and fluidity. Compared with the conventional technology, although conventional anti-settling aids (such as fumed silica, bentonite, montmorillonite, etc.) can improve the anti-settling properties of fillers in colloids, they are often accompanied by problems such as increased viscosity, increased thixotropic ratio, and poor fluidity. The epoxy potting compound prepared by the present invention can significantly improve the anti-settling properties of the powder without significantly increasing the viscosity and thixotropic ratio, and effectively solves the problem of the settling stability of the epoxy potting compound during long-term static storage or transportation. (2) The independently designed star-shaped branched anti-settling agent of the present invention makes the prepared epoxy potting glue product have strong toughness and crack resistance. The surface of the star-shaped branched anti-settling agent contains a relatively long polyurethane chain segment, which improves the surface properties of the powder and has a certain toughening effect on the epoxy potting glue system, and can improve the high and low temperature crack resistance. DETAILED DESCRIPTION

[0013] In order to introduce the present invention in more detail, the present invention is further described and illustrated in conjunction with the following examples. Selected raw materials: Epoxy resin: Nantong Xingchen Synthetic Materials Co., Ltd.; active diluent: Anhui Xinyuan Technology Co., Ltd.; thermal conductive powder: Guangdong Jinge New Materials Co., Ltd.; defoaming agent: Guangdong Fangding New Materials Co., Ltd.; flame retardant: Pusaifu (Qingyuan) Phosphorus Chemical Co., Ltd.; coupling agent SCA-E87M: Nanjing Nengde New Materials Technology Co., Ltd.; anhydride: Zhejiang Nanyang Group Co., Ltd.; polyoxyethylene-propylene oxide copolymer diol: Jiangsu Hai'an Petrochemical Plant; isocyanate: Guangzhou Haoyi New Materials Technology Co., Ltd.; aminosilane: Nanjing Nengde New Materials Technology Co., Ltd.; white carbon black: Guangzhou Jibisheng Technology Industry Co., Ltd.; bentonite: model: 200B Zhejiang Fenghong New Materials Co., Ltd.

[0014] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the star-branched anti-settling agent 1# is replaced with a conventional anti-settling agent bentonite; the other steps and amounts are consistent with those of the example, and the specific preparation method is as follows: (1) Preparation of component A: Add 250g of epoxy resin E-51 into a 2L reactor, heat to 50°C, stir at a speed of 200r / min, slowly add active diluent AGE: 30g, aluminum hydroxide: 650g, bentonite 200B: 15g, defoamer: 3g, flame retardant: 50g, coupling agent: 2g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component A; (2) Preparation of component B: Add 335g of hexahydrophthalic anhydride into a 2L reactor, stir at a speed of 200r / min, slowly add 650g of aluminum hydroxide and 15g of bentonite 200B in sequence, stir and mix evenly, vacuum degas, and cool to room temperature to obtain component B; (3) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0015] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the star-branched anti-settling agent 1# is replaced with fumed silica; the other steps and amounts are consistent with those in the example, and the specific preparation method is as follows: (1) Preparation of component A: Add 250g of epoxy resin E-51 into a 2L reactor, heat to 50°C, stir at a speed of 200r / min, and slowly add 30g of active diluent AGE, 650g of aluminum hydroxide, and fumed silica (primary particle size: 30nm, specific surface area: 200m 2 / g): 15g, defoaming agent: 3g, flame retardant: 50g, coupling agent: 2g, stir and mix evenly, vacuum degassing, and cool to room temperature to obtain component A; (2) Preparation of component B: Add 335 g of hexahydrophthalic anhydride into a 2L reactor and stir at a speed of 200 r / min. Slowly add 650 g of aluminum hydroxide and 15 g of fumed silica in sequence. Stir and mix evenly. Degas in vacuum and cool to room temperature to obtain component B. Preparation of potting compound: Mix component A and component B prepared in the above step in a mass ratio of 1:1, stir evenly, and perform vacuum degassing to obtain thermally conductive flame-retardant epoxy potting compound; (3) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0016] Example 1 (1) Preparation of star-branched anti-settling agent 1# STEP 1: Add 1000g of anhydrous ethanol to a 2L reactor, and gradually add 120g of nano-silicon dioxide (primary particle size: 30nm, specific surface area: 200m 2 / g), after being evenly dispersed, 1.8 g of N-phenyl-3-aminopropyltrimethoxysilane pre-hydrolyzed with deionized water was gradually added dropwise, and the proportion of N-phenyl-3-aminopropyltrimethoxysilane coupling agent in the fumed silica was 1.5%. After the reaction was completed, ethanol was removed by rotary evaporation and dried in a vacuum drying oven at 100° C. to obtain N-phenyl-3-aminopropyltrimethoxysilane-modified nano-silica for standby use; STEP2: Add 1000g of urethane-grade toluene to a 2L reactor, add 100g of N-phenyl-3-aminopropyltrimethoxysilane modified nano-silica prepared in Step 1, stir, then add 1.5g of hydantoin epoxy resin solution, react at 25°C for 0.5h, then add 0.75g of polyether diol (molecular weight M w : 500) and 0.75g of hexamethylene diisocyanate, heat to 65°C, react for 1.5h, pass dry nitrogen throughout the reaction process, after the reaction is completed, wash with solvent and rotary evaporate to obtain star-branched anti-settling agent 1#. (2) Preparation of component A Add 250g of epoxy resin E-51 into a 2L reactor, heat to 50℃, stir at a speed of 200r / min, slowly add active diluent AGE: 30g, aluminum hydroxide: 650g, star-branched anti-settling agent 1#: 15g, defoaming agent: 3g, flame retardant: 50g, coupling agent: 2g, stir to mix evenly, vacuum degas, cool to room temperature, and obtain component A. (3) Preparation of component B Add 335g of hexahydrophthalic anhydride into a 2L reactor, stir at a speed of 200r / min, slowly add aluminum hydroxide: 650g, star-branched anti-settling agent 1#: 15g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component B. (4) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0017] Example 2 (1) Preparation of star-branched anti-settling agent 2# STEP 1: Add 1000g of anhydrous ethanol to a 2L reactor, and gradually add 150g of nano-silicon dioxide (primary particle size: 50nm, specific surface area: 100m 2 / g), after being evenly dispersed, 6.0 g of N-phenyl-3-aminopropyltrimethoxysilane pre-hydrolyzed with deionized water was gradually added dropwise, and the proportion of N-phenyl-3-aminopropyltrimethoxysilane coupling agent in the fumed silica was 4%. After the reaction was completed, ethanol was removed by rotary evaporation and dried in a vacuum drying oven at 100° C. to obtain N-phenyl-3-aminopropyltrimethoxysilane-modified nano-silica for standby use; STEP2: Add 1000g of urethane grade xylene to a 2L reactor, add 100g of N-phenyl-3-aminopropyltrimethoxysilane modified nano-silica prepared in Step 1, stir, then add 3.0g of hydantoin epoxy resin solution, react at 25℃ for 1.0h, then add 1.5g of polyether diol (molecular weight M w :750) and 1.5g of hexamethylene diisocyanate, heat to 65°C, react for 2.0h, pass dry nitrogen throughout the reaction process, after the reaction is completed, wash with solvent, and rotary evaporate to obtain star-branched anti-settling agent 2#. (2) Preparation of component A: Add 200g of epoxy resin E-51 into a 2L reactor, heat to 50°C, stir at a speed of 200r / min, slowly add active diluent AGE: 30g, aluminum hydroxide: 700g, star-branched anti-settling agent 2#: 15g, defoamer: 3g, flame retardant: 50g, coupling agent: 2g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component A; (3) Preparation of component B: Add 285g of hexahydrophthalic anhydride into a 2L reactor, stir at a speed of 200r / min, slowly add aluminum hydroxide: 700g, star-branched anti-settling agent 2#: 15g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component B. (4) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0018] Example 3 (1) Preparation of star-branched anti-settling agent 3# STEP 1: Add 1000g of anhydrous ethanol to a 2L reactor, and gradually add 80g of nano-silicon dioxide (primary particle size: 20nm, specific surface area: 320m 2 / g), after being evenly dispersed, 4.0 g of 3-(N-cyclohexylamino)propyltrimethoxysilane pre-hydrolyzed with deionized water was gradually added dropwise, and the proportion of 3-(N-cyclohexylamino)propyltrimethoxysilane coupling agent in the fumed silica was 5%. After the reaction was completed, ethanol was removed by rotary evaporation and dried in a vacuum drying oven at 105° C. to obtain 3-(N-cyclohexylamino)propyltrimethoxysilane-modified nano-silica for standby use; STEP2: Add 1000g of urethane-grade toluene to a 2L reactor, add 50g of 3-(N-cyclohexylamino)propyltrimethoxysilane-modified nano-silica prepared in Step 1, stir, then add 1.0g of hydantoin epoxy resin solution, react at 25°C for 1.5h, and then add 0.5g of polyether diol (molecular weight M w :250) and 0.5g isophorone diisocyanate, the temperature is raised to 65°C, the reaction is carried out for 2.0h, dry nitrogen is passed through the whole reaction process, after the reaction is completed, the star-branched anti-settling agent 3# is obtained by washing with solvent and rotary evaporation. (2) Preparation of component A: Add 250g of aliphatic epoxy resin into a 2L reactor, heat to 60°C, stir at a speed of 800r / min, slowly add active diluent AGE: 10g, aluminum hydroxide: 642g, star-branched anti-settling agent 3#: 20g, defoamer: 5g, flame retardant: 70g, coupling agent: 3g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component A; (3) Preparation of component B: Add 338g of phthalic anhydride into a 2L reactor and stir at a speed of 800r / min. Slowly add aluminum hydroxide: 642g and star-branched anti-settling agent 3#: 20g in sequence. Stir and mix evenly. Degas in vacuum and cool to room temperature to obtain component B. (4) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0019] Example 4 (1) Preparation of star-branched anti-settling agent 4# STEP 1: Add 1000g of anhydrous ethanol to a 2L reactor, and gradually add 200g of nano-silicon dioxide (primary particle size: 90nm, specific surface area: 80m 2 / g), after being evenly dispersed, 12 g of N-(n-butyl)-3-aminopropyltriethoxysilane pre-hydrolyzed with deionized water was gradually added dropwise, and the proportion of N-(n-butyl)-3-aminopropyltriethoxysilane coupling agent in the fumed silica was 6%. After the reaction was completed, ethanol was removed by rotary evaporation and dried in a vacuum drying oven at 115° C. to obtain N-(n-butyl)-3-aminopropyltriethoxysilane-modified nano-silica for standby use; STEP2: Add 1000g of urethane-grade xylene to a 2L reactor, add 150g of N-(n-butyl)-3-aminopropyltriethoxysilane-modified nano-silica prepared in Step 1, stir, then add 9.0g of hydantoin epoxy resin solution, react at 25°C for 1.5h, then add 4.5g of polyether diol (molecular weight M w : 1500) and 4.5g of isophorone diisocyanate, heat to 55°C, react for 2.5h, pass dry nitrogen throughout the reaction process, after the reaction is completed, wash with solvent and rotary evaporate to obtain star-branched anti-settling agent 4#. (2) Preparation of component A: Add 143g of alicyclic epoxy resin into a 2L reactor, heat to 60°C, stir at a speed of 600r / min, slowly add active diluent AGE: 10g, alumina: 720g, star-branched anti-settling agent 4#: 45g, defoamer: 4g, flame retardant: 75g, coupling agent: 3g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component A; (3) Preparation of component B: Add 235g of phthalic anhydride into a 2L reactor and stir at a speed of 600r / min. Slowly add alumina: 720g and star-branched anti-settling agent 4#: 45g in sequence. Stir and mix evenly. Degas in vacuum and cool to room temperature to obtain component B. (4) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0020] Example 5 (1) Preparation of star-branched anti-settling agent 5# STEP 1: Add 1000g of anhydrous ethanol to a 2L reactor, and gradually add 160g of nano-silicon dioxide (primary particle size: 55nm, specific surface area: 150m 2 / g), after being evenly dispersed, 16 g of bis(3-trimethoxysilylpropyl)amine pre-hydrolyzed by deionized water was gradually added dropwise, the proportion of bis(3-trimethoxysilylpropyl)amine coupling agent in the fumed silica was 10%, after the reaction was completed, ethanol was removed by rotary evaporation and dried in a vacuum drying oven at 115°C to obtain bis(3-trimethoxysilylpropyl)amine modified nano-silica, which was set aside; STEP2: Add 1000g of urethane-grade toluene to a 2L reactor, add 120g of bis(3-trimethoxysilylpropyl)amine-modified nano-silica prepared in Step 1, stir, then add 7.2g of hydantoin epoxy resin solution, react at 25°C for 1.5h, then add 3.6g of polyether diol (molecular weight M w : 1000) and 3.6g hydrogenated MDI, heat to 65°C, react for 3.0h, pass dry nitrogen throughout the reaction process, after the reaction is completed, wash with solvent and rotary evaporate to obtain star-branched anti-settling agent 5#. (2) Preparation of component A: Add 199g of alicyclic epoxy resin into a 2L reactor, heat to 60°C, stir at a speed of 600r / min, slowly add active diluent AGE: 30g, silicon powder: 650g, star-branched anti-settling agent 5#: 45g, defoamer: 10g, flame retardant: 60g, coupling agent: 6g, stir and mix evenly, vacuum degas, cool to room temperature, and obtain component A; (3) Preparation of component B: Add 305g of phthalic anhydride into a 2L reactor and stir at a speed of 600r / min. Slowly add silicon micropowder: 650g and star-branched anti-settling agent 5#: 45g in sequence. Stir and mix evenly. Degas in vacuum and cool to room temperature to obtain component B. (4) Preparation of potting compound: Component A and component B prepared in the above step are mixed and stirred in a mass ratio of 1:1, and vacuum degassed to obtain a thermally conductive flame-retardant epoxy potting compound.

[0021] Epoxy potting test standards and methods Thermal conductivity: using a heat flow thermal conductivity tester, according to ASTME D5470-6 standard, the test was carried out at an ambient temperature of 25°C, a test pressure of 200 psi, a hot end temperature of 65°C, and a sample size of 30 mm in diameter and 2 mm thick. Viscosity and thixotropic ratio: After component A and component B are dispersed evenly, the temperature is kept constant at 25°C, and the viscosity is measured using Brookfield DV2T, rotor: HB-02, speed: 2r, 6r, 12r, 20r, range: 40-80% viscosity; thixotropic ratio: 2r viscosity / 20r viscosity; Leveling: Refer to the national standard GB / T1479-1979 "Determination of consistency of thick paint and putty". After mixing the two components AB, keep the temperature at 25℃ for 1h, take a quantitative volume (20ml) of the sample, put it between two glass plates, use a 2000g weight, press for 60s, remove the weight, and measure the diameter of the sample diffused into a thin sheet from the scale (50-160mm) on the upper glass cover. A smaller diffusion diameter indicates a high consistency, otherwise, it means a low consistency. Static anti-sedimentation test: After the material is dispersed evenly, it is placed in a graduated cylinder and placed in a constant temperature and humidity room at 23±2℃ and 50±5% to observe the oil seepage on the surface of the rubber and the sedimentation of the powder at the bottom; Transport simulation vibration and sedimentation test: refer to the national standard GB / T4857-2003, reciprocating vibration, frequency 300 rpm, amplitude 25.4mm, to simulate the process of sedimentation caused by vibration during transportation of potting glue. High and low temperature cracking performance test: select M12 nut and metal disc (outer diameter 60mm, depth 15mm), place the nut in the middle of the metal disc, inject the matching resin into the metal disc until the resin liquid level is flush with the upper end of the nut wall, and cure according to the curing conditions of the test resin. After stress release and curing, conduct hot and cold shock tests. The test conditions are: -45~120℃, and the test is cyclical until cracks appear.

[0022] The performance test results of the embodiments and comparative examples are shown in Table 1.

[0023] From the test results in Table 1, we can see that: (1) Compared with Comparative Example 1-2, the epoxy potting adhesive in Example 1-5 with the addition of the star-branched anti-settling agent has significantly lower viscosity and thixotropic ratio, and improved leveling properties; (2) The epoxy potting glue comparative examples 1 and 2 both showed soft sedimentation during static placement, and hard sedimentation or even hardening during dynamic anti-settling test. In contrast, the epoxy potting glues of Examples 1-5 to which the star-branched anti-settling agent of the present invention was added showed no sedimentation in both static and dynamic anti-settling tests, and the high and low temperature cracking resistance of the cured products was significantly improved.

[0026] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A weak thixotropic, anti-settling thermally conductive epoxy potting adhesive, characterized in that: The preparation steps are as follows: component A and component B are mixed in a mass ratio of 1:1, stirred evenly, and then vacuum-degassed to obtain the product; The weight percentage of each material in the A component is as follows: The preparation method of component A is as follows: according to the weight percentage, epoxy resin is first added into a reaction kettle, the temperature is raised to 40-70° C., and the speed is stirred at 200-1500 r / min, and each material of component A is added into the epoxy resin, and the mixture is stirred and mixed evenly, and then vacuum degassing is performed to obtain component A; The weight percentage of each material of the B component is as follows: Anhydride: 20-45% Thermal conductive powder: 50-75% Star-branched anti-settling agent: 0.5-5% The preparation method of the B component is as follows: according to the weight percentage, acid anhydride is first added into a reaction kettle, and each material is added into the acid anhydride by stirring at room temperature and a rotation speed of 200 to 1500 r / min, and after stirring and mixing evenly, vacuum degassing is performed to obtain the B component.

2. A weakly thixotropic, anti-settling thermally conductive epoxy potting adhesive according to claim 1, characterized in that: The preparation method of the star-branched anti-settling agent is: STEP 1: Disperse 5 to 25 parts of nano-silica in 100 parts of anhydrous ethanol solvent, with the mass proportion of nano-silica in anhydrous ethanol being 5% to 25%; after uniform dispersion, gradually drop 0.025 to 1.5 parts of aminosilane solution pre-hydrolyzed by deionized water, with the mass proportion of aminosilane in fumed silica being 0.5% to 15%. After the reaction is completed, remove the ethanol by rotary evaporation and dry at a drying temperature of 100 to 150°C to obtain aminosilane-modified nano-silica for standby use; STEP2: Place 10-300 parts of aminosilane-modified nano-silica and 1000 parts of urethane-grade solvent prepared in Step 1 in a dry reaction vessel and stir, then add 0.5-2.0 parts of hydantoin epoxy resin solution, the reaction temperature is 10-30°C, and the reaction time is 0.5-3.0h; then drop 0.5-5.0 parts of polyether diol and isocyanate respectively, and react after the addition is completed, the reaction temperature is 50-75°C, the reaction time is 0.5-3.0h, and dry nitrogen is passed through the whole reaction process. After the reaction is completed, the star-branched anti-settling agent is obtained by washing with solvent and rotary evaporation, wherein the mass proportion of organic components in the fumed silica is 0.5%-15%; The reaction formula for its preparation is as follows: The primary particle size of the nano-silicon dioxide in step 1 is 1 to 100 nm, and the specific surface area is 25 to 500 m 2 / g; The aminosilane in step 1 is a secondary aminosilane, specifically one or more of N-(2-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-(N-cyclohexylamino)propyltrimethoxysilane, N-(n-butyl)-3-aminopropyltrimethoxysilane, N-(n-butyl)-3-aminopropyltriethoxysilane, bis(3-triethoxysilylpropyl)amine, bis(3-trimethoxysilylpropyl)amine, etc.; The urethane grade solvent in step 2 is one of toluene and xylene; The structural formula of the hydantoin epoxy resin in step 2 is as follows, wherein the n value is 1 to 6, and the epoxy value is 0.2 to 0.75 mol / 100 g, preferably 0.44 to 0.70 mol / 100 g; The polyether diol in step 2 is ethylene oxide-propylene oxide diol, and its relative molecular weight is 400-2000; The isocyanate in step 2 is one of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI) or hydrogenated MDI.

3. The weakly thixotropic, anti-settling thermally conductive epoxy potting adhesive according to claim 1, characterized in that: The epoxy resin is one or more of bisphenol epoxy resin, glycidyl ester epoxy resin, aliphatic epoxy resin, alicyclic epoxy resin and heterocyclic epoxy resin.

4. The weakly thixotropic, anti-settling thermally conductive epoxy potting adhesive according to claim 1, characterized in that: The active diluent is one or more of a monofunctional epoxy diluent, a difunctional epoxy diluent and a multifunctional epoxy diluent.

5. The weakly thixotropic, anti-settling thermally conductive epoxy potting adhesive according to claim 1, characterized in that: The thermal conductive powder is one or more of aluminum hydroxide, aluminum oxide, silicon powder, boron nitride, aluminum nitride, diamond, silicon nitride, etc., and its particle size D50 is 0.5-100 μm.

6. The weakly thixotropic, anti-settling thermally conductive epoxy potting adhesive according to claim 1, characterized in that: The acid anhydride is one or more of phthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride and the like.

7. The weakly thixotropic, anti-settling thermally conductive epoxy potting adhesive according to claim 1, characterized in that: The defoaming agent is FD-940, the coupling agent is 3-glycidyloxypropyltrimethoxysilane SCA-E87M, and the flame retardant is a phosphorus-nitrogen flame retardant.

Citation Information

Patent Citations

  • Additive compositions for potting compounds and their applications

    CN111087942B

  • A two-component thermally conductive and flame-retardant epoxy resin potting compound, its preparation method and application

    CN111944468B

Cited By

  • Flexible solar panel and preparation method thereof

    CN120379353A